The Initial Slope of the Variogram, Foundation of the Trabecular Bone Score, Is Not or Is Poorly Associated With Vertebral Strength. (3rd September 2015) - Maquer, Ghislain; Lu, Yongtao; Dall'Ara, Enrico; Chevalier, Yan; Krause, Matthias; Yang, Lang; Eastell, Richard; Lippuner, Kurt; Zysset, Philippe K
ABSTRACT: Trabecular bone score (TBS) rests on the textural analysis of dual‐energy X‐ray absorptiometry (DXA) to reflect the decay in trabecular structure characterizing osteoporosis. Yet, its discriminative power in fracture studies remains incomprehensible because prior biomechanical tests found no correlation with vertebral strength. To verify this result possibly owing to an unrealistic setup and to cover a wide range of loading scenarios, the data from three previous biomechanical studies using different experimental settings were used. They involved the compressive failure of 62 human lumbar vertebrae loaded 1) via intervertebral discs to mimic the in vivo situation ("full vertebra"); 2) via the classical endplate embedding ("vertebral body"); or 3) via a ball joint to induce anterior wedge failure ("vertebral section"). High‐resolution peripheral quantitative computed tomography (HR‐pQCT) scans acquired from prior testing were used to simulate anterior‐posterior DXA from which areal bone mineral density (aBMD) and the initial slope of the variogram (ISV), the early definition of TBS, were evaluated. Finally, the relation of aBMD and ISV with failure load (Fexp ) and apparent failure stress (σexp ) was assessed, and their relative contribution to a multilinear model was quantified via ANOVA. We found that, unlike aBMD, ISV did not significantly correlate with Fexp and σexp, except for the "vertebral body" case ( r 2 = 0.396, p = 0.028). Aside from the "vertebra section" setup where it explained only 6.4% of σexp ( p = 0.037), it brought no significant improvement to aBMD. These results indicate that ISV, a replica of TBS, is a poor surrogate for vertebral strength no matter the testing setup, which supports the prior observations and raises a fortiori the question of the deterministic factors underlying the statistical relationship between TBS and vertebral fracture risk. © 2015 American Society for Bone and Mineral Research.